Gerenciamento de projetos na administração pública: especificações do PMO para desenvolvendo de artefato para seleção e fomento de projetos baseados em inovação frugal - Santos, André Roberto Ramos dos (2023)
Public projects are intended to deliver and realize benefits that have not yet been made available to society, the public administration is responsible for managing, implementing, creating or improving practices in the delivery of these projects. And project management is a real alternative to these desires of public managers. This research work will seek to develop an artifact to support the management of public projects, carrying out an intervention, addressing the theoretical references of PMO - Project Management Office, public administration, project selection, public promotion and frugal innovation, being project selection and innovation frugal the main axes of this research work. Frugal innovation is a concept that emerged in emerging countries, with socioeconomic characteristics very similar to Brazil, especially India and China, mainly due to social deprivation and basic survival needs. Frugal innovation has as its identity improvisation, creative innovation and the need to adapt, seeking a solution to environments with financial constraints, uncertain circumstances and economic insecurity. For this research, we will use a combination of Science research and action research design methods, seeking to understand the problem of the absence of an organized methodology for selecting and promoting public projects with a frugal concept, and proposing the construction of an artifact that can solve this problem. The identification of the problem involved the formation of a research committee, interviews with civil servants and a literature review. Subsequently, the action-research method was used to confirm the usability of the constructed model. This model should be developed and applied in a city hall in greater São Paulo. Seeking to be a didactic method for servers with any level of experience in project management. And how can this artifact forged in concepts of frugal innovation contribute to the management and selection of projects that demand public support? And what are the results of this intervention? in order to understand how this artifact will bring better results in project management for public administration.